Exile, Horizons, and Poetic Language - Saussy, Haun (Social research, 2024)
Exile or banishment has long been a professional liability of intellectuals in many cultures. For practical consequences, it matters whether an offender is exiled to another polity, becoming subject to its laws, or banished to a marginal area of a single world empire. Within the Roman and Chinese Empires, banished poets narrate their predicament in ways that reflect not only their personal histories but also the resources of poetic language whereby disgraced and demoted writers can revise the judgments applied to them.